Distance and displacement inventory: Construction, validation and structural analysis - Akhmad Jufriadi; Sutopo Sutopo; Sentot Kusairi; Sunaryono Sunaryono; Dina Asmaul Chusniyah; Hena Dian Ayu (Universitas PGRI Kanjuruhan Malang, 2024)
This research aims to develop an instrument for assessing understanding distance and displacement concepts. Distance and Displacement Inventory (DDI) is an instrument constructed in multi-representations, including picture, table, graphic, mathematical, and verbal representations. This instrument is in multiple-choice format with ten questions to assess students' understanding of distance traveled and displacement. DDI development refers to R&D design by Borg&Gall and test development flowchart by Beichner. DDI was applied to 357 students in Indonesia who had taken introductory physics courses. Student answers were analyzed to determine the DDI's psychometric properties and structural analysis. The analysis results show that the DDI is adequate for assessing students' understanding of travel distance and displacement concepts. Meanwhile, the structural analysis of students' knowledge results shows that students have different perceptions of each question item according to their representation. Furthermore, students who understand the concept of distance traveled and displacement in one representation may need help understanding it correctly in another representation. This research implies the necessity of designing learning designs based on multi-representations and teaching students about the changes between these representations.